Incident angle–tuned, broadband, ultrahigh-sensitivity plasmonic antennas prepared from nanoparticles on imprinted mirrors1. Issue 9 (4th March 2015) - Yu, Chen-Chieh; Tseng, Yi-Chuan; Su, Pao-Yun; Lin, Keng-Te; Shao, Chang-Ching; Chou, Sin-Yi; Yen, Yu-Ting; Chen, Hsuen-Li
<x xml:space="preserve">Abstract</x> We have used a direct imprint-in-metal method that is cheap and rapid to prepare incident angle-tuned, broadband, ultrahigh-sensitivity plasmonic antennas from nanoparticles (NPs) and imprinted metal mirrors.